The three Mrs. Wrights : a novel - Keir, Linda (Lake Union Publishing, 2020)
"Lark has good things coming: a career as a board-game designer and a whirlwind romance with a handsome investor. Trip is so compassionate and supportive, he's almost too good to be true. Jessica has always been cautious, but she can't resist Jonathan. The brilliant TED-talking visionary has big plans for his inspiring medical start-up. Now Jessica is invited to be part of the team--and to partner with the founder outside the office. Holly has settled into a comfortable life with Jack, her husband of nearly twenty years. They've raised three children, they own a beautiful home, and they've founded a worthy charity. She's proud of building a marriage that has endured--she just doesn't want to look too closely at the cracks. Lark, Jessica, and Holly are three strangers with so much in common it hurts. Their one and only is one and the same. The charming Mr. Wright's serial lies are about to catch up with him..." -- Amazon.